Adição de levedura (Saccharomices cerevisae) na dieta de bovinos de corte em confinamento - Cecilio, Marcos Emanuel Delavi (2018)
The effect of the addition of culture of live yeasts (Saccharomyces cerevisiae) in the high concentrate diet, on the performance, carcass characteristics and physical composition of the meat of cattle in confinement. The animals had a mean weight of (423 kg PV, 18 months of age) and the animals were distributed in individual stalls, remaining 74 days in confinement. The diet was composed of corn silage and concentrate, having a concentrated voluminous ratio of 20:80, (50g / yeast / animal / day) and no additive (control) were used to evaluate the performance in confinement by means of individual evaluation of the consumption, carcass characteristics and physical composition of the meat. There was no effect of the additive (p> 0.05) on intake and carcass characteristics, however, the yeast increased (p< 0.05) the muscle portion of the physical composition of the meat and the yeast-free diet increased (p< 0.05) the percentage of fat. The addition of yeasts (Saccharomyces cerevisiae) does not improve the performance and characteristics of the carcass, but may increase the percentage of the muscle of beef cattle confined with high concentrate diet.